2020
DOI: 10.1097/adm.0000000000000627
|View full text |Cite
|
Sign up to set email alerts
|

Historical Perspective of Proactive and Reactive Regulations of E-cigarettes to Combat Nicotine Addiction

Abstract: Cigarettes and electronic cigarettes (e-cigarettes) are major sources of exposure to nicotine, an addictive chemical. Although these products are being regulated by the Food and Drug Administration (FDA) under the Tobacco Control Act, specifications about the nicotine content in these products have not been established yet. In e-cigarettes, nicotine concentration ranges from 0 to > 50mg/mL, and the recent e-cigarette devices provide control to change nicotine flux for higher nicotine delivery. Due to the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Prior research has also suggested e-cigarette use at least partially related to higher SES 7 27. On the country level, the prevalence of e-cigarette use has been lower among youth in the middle-income and low-income than high-income countries3; however, to contain the situation, ‘proactive’ rather than ‘reactive’ regulations are needed 28 29…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has also suggested e-cigarette use at least partially related to higher SES 7 27. On the country level, the prevalence of e-cigarette use has been lower among youth in the middle-income and low-income than high-income countries3; however, to contain the situation, ‘proactive’ rather than ‘reactive’ regulations are needed 28 29…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, nicotine depending on the pH can be presented as a freebase (non-protonated), mono-protonated, or diprotonated form (Figure 1). The freebase and protonated nicotine yield of the e-cigarettes is found to have different effects on the plasma nicotine concentration-time profile in vapers [36][37][38][39]. As the possible reasons for such differences are being studied, it becomes necessary to determine the freebase or protonated nicotine yield of liquids and classify them based on this yield.…”
Section: Introductionmentioning
confidence: 99%
“…As the possible reasons for such differences are being studied, it becomes necessary to determine the freebase or protonated nicotine yield of liquids and classify them based on this yield. Such classification would eventually help in better regulation of the liquid/e-cigarette market [37,40].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Constituents of e-cigarette liquids such as pulegone, acrolein, formaldehyde, tobacco-specific nitrosamines, and oxidants can also raise the risk of cancer [ 21 ]. E-cigarettes have been on the U.S. market for a little over a decade [ 26 ]. This limits the amount of longitudinal data available to show the long-term effects of this product.…”
Section: Introductionmentioning
confidence: 99%